Exploring the cultural and linguistic dimensions of phraseological somatisms: a comparative analysis of english and uzbek languages (SCIENCE and SOCIETY, 2025)
The article delves deeper into the world of phraseological somatisms in English and Uzbek, providing a comparative analysis of these unique linguistic phenomena. Through a systematic analysis of selected somatic expressions, the role of phraseological somatisms in enriching language use and developing intercultural understanding is highlighted.